Contesting cultural meaning in a post-apartheid South African HIV/AIDS music event - Okigbo, Austin (International Library of African Music, 2014)
On the night of July 29, 2007 a cocktail party was organized by McCord Hospital at the Zimbali Lodge at the Overport in Durban for a leading Harvard AIDs research scientist and his team. In line with what had become customary at the hospital, the Siphithemba Choir, which functions as a support group and choral ensemble at the hospital, was invited to perform at the event. At the party the choir performed several gospel tunes, including an adaptation of Enoch Sontongas Nkosi Sikelel'iAfrika, and some of their own compositions. Two traditional Zulu songs, Isiyalo (Advice) and Ikhalaphi (From whence the cry), however, stood out most. Their performance styles affected the configuration of the night's music event, thus informing the discourse that is central to this paper. The two traditional songs share commonalities on a number of levels. First, they are both in rudimentary African call and response style, with Ikhalaphi having two distinct spoken A and sung B sections. Second, the lyrics of each song address the HIV/AIDS issue. Isiyalo speaks about a young beautiful woman who engages in the prostitution trade and rejects the men who propose marriage to her. Ikhalaphi sings about a female lover whose sagged breasts are clear indications that she has become sexually active before marriage. Thus the two songs touch on the theme of sexuality, which is integral to HIV/AIDS discourse, particularly in regards to disease prevention. Finally, they both integrate Zulu ngoma dance.
Keywords: South Africa; African Music